2016
DOI: 10.1177/2333721415626888
|View full text |Cite
|
Sign up to set email alerts
|

Direct Care Worker Training to Respond to the Behavior of Individuals With Dementia

Abstract: Only a handful of online training programs are available for direct care workers (DCWs) to acquire the strategic skills needed to improve dementia care in instances of challenging or inappropriate behavior. Utilizing pre- and post-test data from a convenience sample of 40 DCWs, the present study sought to determine (a) whether DCWs’ knowledge of responding to dementia-related behavior increased following participation in the CARES® Dementia-Related Behavior™ Online Training Program (or CARES® Behavior) and (b)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…Pets, cabins and cars were often selected. Previous studies have found that reminiscence helps to improve communication between PWMLs and their caregivers [35]. Similarly, when family members participated in reminiscence with PWMLs in the current study, PWMLs’ verbal engagement occurred as well.…”
Section: Discussionsupporting
confidence: 63%
“…Pets, cabins and cars were often selected. Previous studies have found that reminiscence helps to improve communication between PWMLs and their caregivers [35]. Similarly, when family members participated in reminiscence with PWMLs in the current study, PWMLs’ verbal engagement occurred as well.…”
Section: Discussionsupporting
confidence: 63%
“…Finally, the high levels of satisfaction with the curriculum content and delivery bode well for its future uptake. Our findings are concordant with a previous study of the effectiveness and acceptability of an e-learning curriculum among direct care providers working with older adults with dementia, as well as studies focused on e-learning among nurses working in other settings ( Almost et al, 2019 ; Gaugler et al, 2016 ; McDonald et al, 2018 ; Voutilainen et al, 2017 ).…”
Section: Discussionsupporting
confidence: 92%
“…The training needs about dementia care of staff members who are not involved in direct care services but working within care settings are ignored. Previous studies on dementia care training mainly focused on health professionals, direct care workers, and healthcare students [2,5,6,8,14,24]. Given that people with dementia interact with different staff members in the care environment, their reactions and responses would also be influential to care recipients' wellbeing and thus care quality.…”
Section: Discussionmentioning
confidence: 99%